(untitled) (Proceedings of the Society of Antiquaries of Scotland, 2021)
Professor John Coles, who died on 14 October 2020 aged 90, had a long and distinguished career as a prehistorian, experimental archaeologist and wetland archaeologist, and he made substantial contributions to Scottish archaeology, as well as to European and world archaeology more generally.